Correction: Towards wireless highly sensitive capacitive strain sensors based on gold colloidal nanoparticles. Issue 24 (11th June 2018) - Nesser, H.; Grisolia, J.; Alnasser, T.; Viallet, B.; Ressier, L.
Abstract : Correction for 'Towards wireless highly sensitive capacitive strain sensors based on gold colloidal nanoparticles' by H. Nesser et al., Nanoscale, 2018, DOI: 10.1039/c7nr09685b.